Pengaruh Model Think Pair Share Berbantuan Animasi Terhadap Hasil Belajar Siswa Ditinjau Dari Minat Belajar Siswa Kelas XI SMAN 1 Mojolaban Pada Pembelajaran Ekonomi - Adila Septi Astuti; Kristiani Kristiani; Sudarno Sudarno (Journal on Education, 2023)
This study aims to determine the effect of applying the Think Pair Share (TPS) learning model assisted by animation on learning outcomes in terms of learning interest in class XI students of SMAN 1 Mojolaban. The data analysis technique uses the Paired Sample T Test and the Two Way Anova test. The results of the study are as follows (1) the TPS learning model influences the learning outcomes of class XI IPS students at SMAN 1 Mojolaban. (2) The animation-assisted TPS model has no effect on learning outcomes in terms of student learning interest. This is evident from the tcount value of -10,812 (> ttable) and Fcount = 1.257 (<Ftable). Based on this, it can be concluded that the application of the animation-assisted TPS learning model has a positive and significant effect on students' cognitive learning outcomes, but has no effect on student learning outcomes in terms of learning interest in class XI IPS students of SMAN 1 Mojolaban. Theoretically, the research results provide insight and knowledge regarding the influence of the TPS model and animated media on learning outcomes in terms of student interest. While practically proving that there is an influence of the animation-assisted TPS model on learning outcomes, it has no effect on learning outcomes in terms of interest.